Design and dynamic performance analysis of high-contact-ratio spiral bevel gear based on the higher-order tooth surface modification. (July 2021) - Mu, Yanming; He, Xueming
Highlights: Higher-order tooth surface modificationmethod related tohigh contact ratio. Meshing impactanalysis ofspiral bevel gear consideringbase pitch difference. Ease-offflank modificationbased on dynamic performance ofspiral bevel gear. Flank modificationaimingat reducing loaded transmission errorand meshing impact. Abstract: To reduce the running vibration of high-contact-ratio (HCR) spiral bevel gear transmissions, an innovative higher-order tooth surface modification (HTSM) method is proposed to reduce the vibration excitation of gear transmission. First, according to the meshing characteristic of HCR spiral bevel gear transmissions, an innovative modification curve is proposed. Second, the auxiliary tooth surface modification (ATSM) method is used to generate the higher-order modified spiral bevel gear. Third, the loaded transmission error (LTE) and meshing impact (MI) of higher-order modified spiral bevel gear transmissions are calculated based on the LTCA method and the impact theory while considering tooth deformation. Last but not least, based on the ease-off technology, an optimization model is built to reduce the LTE and MI of HCR spiral bevel gear transmissions. Through simulation analysis, it is found that compared with the second-order modified spiral bevel gear, the high-order tooth surface modification method can not only effectively reduce the LTE, MI and dynamic load factor (DLF) of HCR spiral bevel gear, but also improve its dynamic performance within full speed range. This study provides an effective way for improving the dynamic performance of HCR spiral bevel gear transmissions within full speed range.